Borderline personality disorder and emotion dysregulation (BioMed Central, 2014)
"Borderline Personality Disorder and Emotion Dysregulation provides a platform for researchers and clinicians interested in borderline personality disorder (BPD) as a currently highly challenging psychiatric disorder. Emotion dysregulation is at the core of BPD but also stands on its own as a major pathological component of the underlying neurobiology of various other psychiatric disorders. The journal focuses on the psychological, social and neurobiological aspects of emotion dysregulation as well as epidemiology, phenomenology, pathophysiology, treatment, neurobiology, genetics, and animal models of BPD."